Development, validation of competency questionnaire, analysis of its predictors and mediators for the adoption of health information system amongst nurses in Hospital Universiti Sains Malaysia - Aziz, Naveen Azizen (2023)
Introduction: This study builds upon the importance of robust health systems in the wake of a pandemic and the need for increased organisational readiness for change, particularly in the Malaysian healthcare sector. The effectiveness and suitability of instruments employed to gauge organisational readiness have been the subject of considerable discussion and contention. Despite efforts to assess organisational readiness, over 70% of organisational change management initiatives fail to achieve their intended goals because of employee resistance and insufficient support from the management. This study focuses on the competency component of organisational readiness and its significance in facilitating digital health adoption. Digital health adoption failure has been widely documented in developed and developing economies. This study examined staff competencies, the predictors and mediators that influence employees’ competencies necessary for health information systems. The first objective was to develop and validate a competency questionnaire that forms a component of organizational readiness for health information system adoption among nurses in Hospital University Sains Malaysia (USM) in Kelantan, Malaysia. Followed by which the second objective determined the current competency level utilising the developed and validated questionnaire. The third objective was to identify the predictors while the final objective was to identify the mediating factors associated with the current competencies amongst nurses. Methods: After generating the items, a cross sectional study was conducted with 180 nurses, and an exploratory factor analysis was conducted to reduce the number of items and identify the latent constructs, followed by the recruitment of 305 nurses for confirmatory factor analysis (CFA) and evaluation of construct validity. The study continued with the recruitment of 420 nurses from hospital USM to assess the current staff competency for health information system adoption. Linear regression was conducted to identify the potential predictors that influenced competencies. Two mediation models were analysed to identify the mediators that influenced nurses’ competencies in the adoption of health information systems. Results: The final model for competency comprised of 18 items, which demonstrated a good model fit, as suggested by the CFA. The questionnaire displayed excellent convergent and discriminant validity, with all constructs having a correlation coefficient greater than 0.7 for domains with three or more items. The mean values for the Individual domains of Knowledge, Skill, and Attitude are 16.8, 11.0, and 31.0 respectively, with corresponding standard deviations of 3.04, 2.06, and 5.64. Similarly, the mean values for the Team domains of Knowledge, Skill, and Attitude are 15.6, 9.6, and 8.5 respectively, with corresponding standard deviations of 3.01, 2.08, and 2.44. The results for the Individual, Team, and Staff competencies were found to have mean scores of 58.6, 33.8, and 92.4 respectively, with corresponding standard deviations of 9.50, 6.21, and 13.9. In the regression analysis, no predictors were found to explain current staff competency. However, mediation analysis revealed that positional grade served as a mediating factor in the relationship between age and years of experience, mediating the effects of the two variables on staff, individual, and team competencies through competitive mediation classified under partial mediation. Conclusion: The competency questionnaire demonstrated exceptional psychometric properties with adequate validity and reliability and is thus suitable for use in any study pertaining to the adoption of health information systems among nurses. Additionally, the study identified grade as a potential mediator that exhibits competitive mediation effects through age and years of experience, respectively, to influence competencies related to the adoption of health information systems.